The tribe Phaseoleae s.l. (Leguminosae-Papilionoideae) in the municipality of Caetité, Bahia State, Brazil - Teixeira, Jaqueline Dias (2021)
Phaseoleae s.l. comprises the largest tribe of subfamily Papilionoideae in number of genera, with 89 genera and 1,567 species. Regional taxonomic studies of the tribe are only occasional in Brazil and rare in Northeastern Brazil, including Bahia, the region’s most species-rich state. In this context, the present study had as its objective to carry out a taxonomic study of the species of Phaseoleae s.l. occurring in Caetité (BA), a conservation priority region for the Caatinga vegetation. For this purpose, we made field expeditions and visited to the HUNEB-Collection Caetité and HUEFS Herbaria. A total of 25 species and 15 genera were recorded, accounting for 23% of the species registered for Bahia. Caetité stands out as one of the main centers of floristic richness of Phaseoleae s.l. in the semi-arid region of Bahia state. Leaflet shape, inflorescence type and the coloration of the petals and seeds are the most useful characters for identification.